(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Charles Everett Koop was a great Surgeon General, probably the most influential in the history of the United States of America. He never missed courage in his life and often he had used it to tackle professional and personal tough problems. In his public activity, he faced controversial health problems of American people as smoking, abortion and the first occurrence of the epidemic Acquired Immune Deficiency Syndrome (AIDS). Koop was a rigorous man. The lodestar that guided Koop in his work, as a public servant was to do the best for health of Americans. In his prestigious and difficult role, he faced the pressing problems of health of millions of people trying to avoid political influence. During his mandate of eight years, Koop increased the influence and authority of his role. His appearance and behaviour were unmistakable: Lincolnesque beard and uniform, conduct hard and pure, exclusively oriented to the health of citizens, over the personal conveniences, political pressure and lobbying. An exemplary man, who for his passion for medicine and his sincere interest in promoting public health, was affectionately considered the "Family Doctor of America".